Enhancing Healthcare Record Modeling Through Graph Convolutional Networks: Overcoming Challenges and Advancing Data Management and Analysis (JOURNAL OF SOFTWARE ENGINEERING TOOLS & TECHNOLOGY TRENDS, 2023)
Modeling healthcare records data as a graph database presents various challenges due to the complex nature of healthcare information and its interconnectedness. In this research endeavor, our primary objective is to pinpoint the major obstacles within this field and present potential remedies to tackle them effectively. By leveraging machine learning techniques, we aim to enhance the efficiency and accuracy of healthcare record modeling, facilitating better data management and analysis. One suitable algorithm for addressing these challenges is the Graph Convolutional Network (GCN). GCN is a deep learning algorithm that operates on graph-structured data, making it well-suited for modeling healthcare records represented as a graph database. GCN allows information propagation between interconnected nodes, capturing the dependencies and relationships within the data. To apply GCN to healthcare record modeling, we can represent patient records as nodes in the graph, with edges indicating various relationships, such as diagnoses, treatments, and patient demographics. The algorithm can then learn the node embeddings, which encode the underlying features of each record, by propagating and aggregating information through the graph. The proposed GCN algorithm can address several challenges in modeling healthcare records as a graph database. Firstly, it can handle the heterogeneous nature of healthcare data by capturing different types of nodes and edges. Additionally, GCN demonstrates a strong capability to capture data dependencies and patterns, enhancing the precision of predictions and recommendations. Additionally, the algorithm can handle missing or incomplete data by leveraging the information from neighboring nodes. We can overcome the challenges associated with modeling healthcare records data as a graph database by utilizing machine learning algorithms such as GCN. These advancements can improve the management and analysis of healthcare data, leading to better patient care, efficient resource allocation, and more informed decision-making in the healthcare domain.